Naphthalene Removal with Layered Double Hydroxides - Butenko, Eleonora; Dan, Olena; Kapustin, Alexey; Neverova-Dziopak, Elena (Geomatics and Environmental Engineering, 2020)
Naphthalene is a hazardous pollutant. It has a negative impact on human health and environment. Its manufacturing process is accompanied by gaseous naphthalene emissions into the air of the premises and then into the atmosphere, thus polluting the environment. There is currently no existing method to remove naphthalene from the gas phase which is capable of meeting the required environmental standards. The goal of this research was to investigate the mechanism of naphthalene removal from the gas phase by the sorption method using Mg/(Al+Mg) layered double hydroxides (LDHs) and to develop naphthalene removal technology to meet the required environmental standards. The methods for obtaining selective sorbents of naphthalene and its derivatives have been investigated. The technology of naphthalene removal from gas phase using Mg/(Al+Mg) LDHs has been developed. The technological parameters of reactors have been calculated. The final concentration of naphthalene of 12 mg/m3 was obtained which appeared to be lower than the maximum allowed concentration. The efficiency of naphthalene sorption with LDHs was found to be over 95%.